Bactericidal efficacy of tissue tolerable plasma on microrough titanium dental implants: An in‐vitro‐study. Issue 6 (9th September 2015) - Preissner, Saskia; Wirtz, Henrik C.; Tietz, Anne‐Kristin; Abu‐Sirhan, Shady; Herbst, Sascha R.; Hartwig, Stefan; Pierdzioch, Philipp; Schmidt‐Westhausen, Andrea Maria; Dommisch, Henrik; Hertel, Moritz
Abstract : Surface decontamination remains challenging in peri‐implant infection therapy. To investigate the bactericidal efficacy of tissue tolerable plasma, S. mitis biofilms were created in vitro on 32 microrough titanium dental implants. Biofilm imaging was performed by confocal laser scanning microscopy (CLSM) and scanning electron microscopy (SEM). The implants were either rinsed with 1% NaCl as negative control (C) or irradiated with a diode laser (DL) for 60 sec as positive control or plasma (TTP60, TTP120) for 60 or 120 sec. Subsequently, colony forming units (CFU) were counted. Post‐treatment, implants were further examined using fluorescence microscopy (FM). Median CFU counts differed significantly between TTP60, TTP120 and C (2.19 and 2.2 vs. 3.29 log CFU/ml; p = 0.012 and 0.024). No significant difference was found between TTP60 and TTP120 ( p = 0.958). Logarithmic reduction factors were (TTP60) 2.21, (TTP120) 1.93 and (DL) 0.59. Prior to treatment, CLSM and SEM detected adhering bacteria. Post‐treatment FM recorded that the number of dead cells was higher using TTP compared to DL and C. In view of TTP's effectiveness, regardless of resistance patterns and absence of surface alteration, its use in peri‐implant infection therapy is promising. The results encourage conducting clinical studies to investigate its impact on relevant parameters.Experimental Design Abstract : Following biofilm formation, implants were either rinsed with 1%NaCl or irradiated with a laser or plasma, and CFUs were counted. Biofilm imaging was performed before and after treatment. CFU numbers were significantly lower after using plasma. Prior to treatment, adhering bacteria were detectable. Post‐treatment imaging recorded that the number of dead cells was higher after using plasma. In view of plasma's efficacy, its use in peri‐implant infection therapy is promising.